Epoxy resin doped with Coumarin 6: Example of accessible luminescent collectors. (April 2017) - Sottile, Matteo; Tomei, Giovanni; Borsacchi, Silvia; Martini, Francesca; Geppi, Marco; Ruggeri, Giacomo; Pucci, Andrea
Graphical abstract: Highlights: Coumarin 6 was efficiently dispersed in Epoxy slabs up to 150 ppm. Calorimetry and spectroscopy determined slab structure and homogeneity. Optically efficiencies 10% greater than that of PMMA collectors were obtained. The research promotes application in the field of solar collectors. Abstract: We report on the preparation of luminescent collectors based on epoxy resins containing Coumarin 6 as fluorescent dye. Fluorescent epoxy slabs were obtained by carefully mixing from 60 to 150 ppm of the fluorophore with bisphenol A diglycidyl ether and 4, 4′-methylenebis(2-methylcyclohexylamine) as curing agent. Spectroscopic (FT-IR, solid-state NMR, Raman) investigations and calorimetric analysis evidence the success of the preparation procedure in terms of slab homogeneity, fluorophore dispersibility and its role in promoting the crosslinking extent. The concentrating ability and the derived optical efficiencies of the epoxy-based collectors are determined with a properly designed set-up and result greater (∼10%) than that of poly(methyl methacrylate) concentrators with the same fluorophore and geometry. Optical efficiencies as high as 7.4% are obtained and enable the potential use of epoxy resins as bulk thermosetting materials for solar collectors.